2011
DOI: 10.1111/j.1365-2141.2011.08945.x
|View full text |Cite
|
Sign up to set email alerts
|

Biological determinants of bleeding in patients with heterozygous factor XI deficiency

Abstract: Summary Bleeding risk is not predictable in patients with factor XI (FXI; F11) deficiency. In this prospective study, our objectives were to determine the biological determinants for bleeding risk in patients with heterozygous FXI deficiency. Patients were classified as either bleeding patients or non‐bleeding patients by calculating the bleeding score (BS) described for von Willebrand disease. Primary haemostasis, thrombin generation, thromboelastometry, procoagulant proteins, inhibitors, fibrinolysis, and F1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 23 publications
3
53
0
1
Order By: Relevance
“…Consistent with published work, standard coagulation assays including FXI:C levels did not allow discrimination between bleeder and nonbleeder groups. 4,5,17,30 In contrast, TGA parameters (ETP and peak height) identified statistically significant differences between bleeder and nonbleeder groups in all sample conditions. However, only in PRP with CTI samples did the 2 groups become well separated on frequency plots.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Consistent with published work, standard coagulation assays including FXI:C levels did not allow discrimination between bleeder and nonbleeder groups. 4,5,17,30 In contrast, TGA parameters (ETP and peak height) identified statistically significant differences between bleeder and nonbleeder groups in all sample conditions. However, only in PRP with CTI samples did the 2 groups become well separated on frequency plots.…”
Section: Discussionmentioning
confidence: 75%
“…[15][16][17][18] Two studies concluded that the TGA was unable to differentiate between bleeder and nonbleeder groups. However, those studies either did not inhibit contact activation (PPP without CTI at TF 1 pM, PRP without CTI at TF 0.5 pM) 17 or were performed in the absence of platelets (PPP with CTI at TF 1 pM), 18 and in both studies the cohorts were smaller than our own and different criteria were used to determine bleeding tendency. In contrast, a third study concluded that thrombin generation measured with TF 1 pM in PPP without CTI samples was able to distinguish between bleeders and nonbleeders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of global assays as a tool to monitor and /or predict individual bleeding risk in FXIdeficient patients is still uncertain due to small sample size, different FXI activity levels and genotypes. In addition, no assay standardization has been achieved with respect to the use of PPP, PRP, TF, phospholipids or CTI [11,12,14,18,19]. Based on our data, the TF concentration used for TG assay is critical since different concentrations of TF may affect the sensitivity of the assay.…”
Section: Discussionmentioning
confidence: 97%
“…Il semble, qu'à l'instar de l'hémophilie, ce test soit utile pour évaluer le risque hémorragique chez un patient donné, qui n'est pas corrélé de faç on constante avec le taux de facteur Willebrand [28]. Les autres déficits congénitaux ont principalement fait l'objet d'articles disparates concernant, encore une fois, l'intérêt du TGT dans l'évaluation du risque hémorragique avec des résultats mitigés, semble-t-il négatifs dans les cas des facteurs VII [29] et XI [30] mais positifs dans le cas du facteur X [31]. De faç on anecdotique, on retrouve des études sur les pathologies plaquettaires [32] et les pathologies acquises de l'hémostase [33].…”
Section: Tgt Et Management Du Risque Hémorragiqueunclassified